BlaNDM-21, a new variant of blaNDM in an Escherichia coli clinical isolate carrying blaCTX-M-55 and rmtB. (14th June 2018) - Liu, Lu; Feng, Yu; McNally, Alan; Zong, Zhiyong
Abstract: Objectives: New Delhi MBL (NDM) is a type of carbapenemase; 20 variants of NDM have been identified to date. We have found a new variant of NDM, NDM-21, and describe it here. Methods: A carbapenem-resistant Escherichia coli was subjected to WGS using an Illumina X10 sequencer to identify the antimicrobial resistance genes and its ST. The gene encoding the new variant of NDM was cloned into E. coli DH5α, with bla NDM-5 being cloned as the control. Transformants were tested for susceptibility to carbapenems. Mating was performed to obtain the plasmid carrying the new bla NDM gene and the complete plasmid sequence was obtained using long-read MinION sequencing. Results: The E. coli isolate belonged to ST617 and phylogenetic group A. It had a gene encoding NDM-21, a new NDM variant. NDM-21 differs from NDM-5 by a Gly-to-Ser amino acid substitution at position 69 (G69S). NDM-21 retains the same activity against carbapenems as NDM-5. bla NDM-21 is carried by a 46.1 kb IncX3 plasmid, which is self-transmissible, and is located in a complex genetic context as bla NDM-5 . The isolate also carried bla CTX-M-55, which encodes an ESBL conferring resistance to aztreonam (which completed its resistance to all clinically available β-lactams), and rmtB, which mediates high-level resistance to aminoglycosides, on an IncFII plasmid. Conclusions: A new NDM variant has been identified and bla NDM-21 has evolved from bla NDM-5 on an IncX3 plasmid.